Figs. 1–7 in A new species of the genus Lathrobium Gravenhorst, 1802 (Coleoptera: Staphylinidae, Paederinae) from the northern part of Kamchatka kray - Ryabukhin, A.S. (Zenodo, 2018)
Figs. 1–7. Lathrobium (Lathrobium) kamenum sp. n. 1, 2 – aedeagus: 1 – lateral view; 2 Published as part of Ryabukhin, A.S., 2018, A new species of the genus Lathrobium Gravenhorst, 1802 (Coleoptera: Staphylinidae, Paederinae) from the northern part of Kamchatka kray, pp. 15-18 in Far Eastern Entomologist 354 on page 16, DOI:10.25221/fee.354.2, http://zenodo.org/record/7164085